Inclusion effect of sago flour in diet on growth performance of broiler quails (Coturnix coturnix japonica) - Mohd Sabri, Muhammad; Hassan, M. N. (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2018)
Sago product has been identified as a potential carbohydrate source for poultry feed. The objective of this experiment is to determine the effect of different substitution level of sago flour in the diet on growth performance of quail. Ninety, mix sexes, day old quails were allocated into 3 treatment groups; Control (100% normal broiler diet, Cn), Treatment 1 (10% sago flour substitution - S10) and Treatment 2 (20% sago flour substitution -S20). Each treatment consists of 3 replications and housed in multiple battery raised floor cage system with 10 chicks per replication per cage. Substitution of sago flour in the diets significantly (P>0.05) affected the total feed intake but did not give any negative effect on the overall growth performance and carcass weight of quails. These observations clearly showed the potential of using sago as a food component in poultry feed particularly quail. In conclusion, sago flour could be in feeding poultry particularly quails. Further study should be done on the optimum inclusion level of sago flour in the feed to maximize the yield of the meat.